Optimize the Power Consumption and SNR of the 3D Photonic High-Radix Switch Architecture Based on Extra Channels and Redundant Rings - Jie Jian; Mingche Lai; Liquan Xiao (Journal of Computer Networks and Communications)
The demand from exascale computing has made the design of high-radix switch chips an attractive and challenging research field in EHPC (exascale high-performance computing). The static power, due to the thermal sensitivity and process variation of the microresonator rings, and the cross talk noise of the optical network become the main bottlenecks of the network’s scalability. This paper proposes the analyze model of the trimming power, process variation power, and signal-to-noise ratio (SNR) for the Graphein-based high-radix optical switch networks and uses the extra channels and the redundant rings to decrease the trimming power and the process variation power. The paper also explores the SNR under different configurations. The simulation result shows that when using 8 extra channels in the 64×64 crossbar optical network, the trimming power reduces almost 80% and the process variation power decreases 65% by adding 16 redundant rings in the 64×64 crossbar optical network. All of these schemes have little influence on the SNR. Meanwhile, the greater channel spacing has great advantages to decrease the static power and increase the SNR of the optical network.